2010
DOI: 10.1111/j.1365-2036.2010.04523.x
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of shortening the dosing interval to once every six weeks in Crohn’s patients losing response to maintenance dose of infliximab

Abstract: SUMMARY BackgroundPatients treated with infliximab for Crohn's disease (CD) frequently require intensified dosage due to loss of response. There are scant data regarding the efficacy of shortening the dosing interval to 6 weeks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 85 publications
(87 citation statements)
references
References 17 publications
2
82
0
1
Order By: Relevance
“…13 An increase in IFX dose to 10 mg/kg or reduction of the intervals of IFX infusion at 4 or 6 weeks represent effective strategies to rescue the response after loss of response. 7,14,15 On the other hand, switching to an alternative anti-TNF-a drug is an effective strategy and is currently considered one of the best options in patients intolerant to their primary anti-TNF-a therapy. From the viewpoint of health economics, it is preferable to establish a strategy for preventing loss of response to IFX.…”
Section: Introductionmentioning
confidence: 99%
“…13 An increase in IFX dose to 10 mg/kg or reduction of the intervals of IFX infusion at 4 or 6 weeks represent effective strategies to rescue the response after loss of response. 7,14,15 On the other hand, switching to an alternative anti-TNF-a drug is an effective strategy and is currently considered one of the best options in patients intolerant to their primary anti-TNF-a therapy. From the viewpoint of health economics, it is preferable to establish a strategy for preventing loss of response to IFX.…”
Section: Introductionmentioning
confidence: 99%
“…A modifi ed ELISA, employing anti-human λ antigen detection antibody (AHLC), has an improved capacity for detection of ATI in presence of IFX, a well as for detection of IgG4 ATI [35]. Such "double positive" results were reported in 9% of patients, and were associated with a trend towards a higher future risk of development of LOR [36]. An opposite state of "double negativity" (IFX-ATI-), frequently reported by an early generation ELISA assay, is signifi cantly less frequently detected with the AHLC assay (13 vs 35.5%, P<0.001).…”
Section: Evaluation Of Serum Levels and Atismentioning
confidence: 99%
“…A pharmacokinetic modeling study in patients with rheumatoid arthritis suggested that interval reduction would provide a more eff ective drug level AUC compared to the equivalent dose increase [53]. However, retrospective studies comparing dose augmentation with shortening of the interval did not demonstrate any signifi cant diff erence in the rates of regained response in CD [36,54] or UC [55].…”
Section: Therapeutic Drug Monitoring (Tdm) For Primary Nonresponsementioning
confidence: 99%
“…Ugyanakkor egyértelmű, hogy a dózis emelése azokban a betegekben lehet sikeres, akik nem vagy csak alacsony gyógyszer-koncentrációval rendelkeznek. Többféle lehetőség létezik IFX-terápia esetén, amelyek nem térnek el jelentősen egymástól, így IFX-et lehet 10 mg/kg dózisban adni nyolchetente vagy 5 mg/kg-ot négyhetente [59]. Ezzel szemben ADAterápia alkalmazásakor az adagolási intervallum csökken-tése az egyetlen rendelkezésre álló lehetőség.…”
Section: A Gyógyszerellenes Antitestek éS a Szérumgyógyszerszint Jeleunclassified